Estudo de viabilidade técnica e financeira da implantação de sistemas de geração de energia elétrica distribuída em tubulações de água no setor de mineração - Andrey Guedes Chagas (2020)
Hydroelectricity is a consolidated and competitive type of renewable energy that plays a strategic role in the global energy matrix and presents several advantages over most other sources of electricity, such as high reliability, proven technology, high efficiency, low maintenance costs and flexibility. Recently, due to the development of compact and specific microturbines for urban application, it is possible to harness the energy of the water in pipes of the water distribution system, in the industrial sector or urban centers for power generation. These turbines are capable of operating in a wide range of flow conditions from pipes from 80mm up to 150mm diameter and can be used in series to increase power output. The electricity generated in pipes has become an interesting alternative for the integration of renewable energy sources and the scenario of distributed generation of energy, added to the photovoltaic and wind systems. It is a source of clean energy, continuous and without environmental impacts, not having, in most cases, the intermittent generation of energy, as in the case of wind and solar energy. Another advantage of this system is related to the high pressure issues in the water pipes that are currently solved with pressure reduction valves. These valves can be replaced by hydraulic turbines installed in the pipes, producing electrical energy. The aim of this work is to evaluate the application of this form of distributed energy generation in Brazil, in which the subject is very little explored and has a wide field of application, through a feasibility study based on the water distribution sector and conducting a survey of the potential of generation hydroelectric power generation in an iron ore mining, comparing the feasibility of applying turbines x pumps as turbine (PaT), and comparing their viability with other sources of distributed power generation.